PENGARUH HARGA, PROMOSI DAN ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TIKTOK SHOP (Studi Kasus Mahasiswa Universitas Surakarta) - Elfani, Rantisa; Trisnowati, Juni (Universitas Of Surakarta, 2024)
The purpose of this study was to determine the effect of price, promotion, and electronic word of mouth on the purchasing decisions of Tiktok Shop consumers (Case study of Surakarta University students), either partially or simultaneously. This research is a quantitative research. The sampling technique used was purposive sampling, with a sample of 100 respondents from undergraduate students in February 2023. Primary data was obtained from questionnaires that had been distributed via the Google form. The analysis technique used is descriptive analysis, multiple linear regression, F test, t test, and determination test (R2). Based on the F test and t test, the results obtained were that the variables of price, promotion, and electronic word of mouth partially or simultaneously had a positive and significant effect on the purchasing decisions of TikTok Shop consumers (Case study of Surakarta University students)